High Exploratory Phenotype Rats Exposed to Environmental Stressors Present Memory Deficits Accompanied by Immune-Inflammatory/Oxidative Alterations: Relevance to the Relationship Between Temperament and Mood Disorders - Lima, Camila Nayane de Carvalho; da Silva, Francisco Eliclécio Rodrigues; Chaves Filho, Adriano José Maia; Queiroz, Ana Isabelle de Gois; Okamura, Adriana Mary Nunes Costa; Fries, Gabriel Rodrigo; Quevedo, João; de Sousa, Francisca Cléa F; Vasconcelos, Silvania Maria Mendes; de Lucena, David F; Fonteles, Marta Maria de França; Macedo, Danielle S. (Frontiers in Psychiatry, 2019)
Low-exploratory (LE) and high-exploratory (HE) rodents mimic the human depressive and hyperthymic temperaments. Mood disorders (MD) may be developed by the exposure of these temperaments to environmental stress (ES). Psychiatric symptoms severity in MD patients is related to the magnitude of memory impairment. Thus, we aimed at studying the consequences of the exposure of LE and HE male Wistar rats, during periadolescence, to a combination of two ES, namely paradoxical sleep deprivation (PSD) and unpredictable stress (US), on memory performance. We also evaluated the prevention of memory alterations by lithium and valproate and hippocampal immune-inflammatory/oxidative, as consequences of ES. HE+ES- and LE+ES-rats presented working (WM) and declarative memory (DM) deficits. Valproate and lithium prevented WM deficits. Lithium prevented DM impairment in HE+ES-rats. Hippocampal glutathione (GSH) was 4-fold increased in HE+ES-rats, being prevented by valproate and lithium. All groups of LE+ES-rats presented increased levels of GSH in relation to controls. Increments in lipid peroxidation in LE+ES- and HE+ES-rats were prevented by valproate in HE+ES-rats and by both drugs in LE+ES-rats. Nitrite levels were increased in HE+ES- and LE+ES-rats (5-fold increase), which was prevented by both drugs in LE+ES-rats. HE+ES-rats presented a two-fold increase in the inducible nitric oxide synthase (iNOS) expression that was prevented by lithium. HE+ES-rats showed increased hippocampal and plasma levels of interleukin (IL)-1 and IL-4. Indoleamine 2, 3-dioxygenase 1 (IDO1) was increased in HE+ES- and LE+ES-rats, while tryptophan 2,3-dioxygenase (TDO2) was increased only in HE+ES-rats. Altogether, our results suggest that LE- and HE-rats exposed to ES present memory deficits, with HE+ES-rats presenting more brain and plasma inflammatory alterations that are partially prevented by mood-stabilizing drugs.